2015
DOI: 10.1002/2015gc005911
|View full text |Cite
|
Sign up to set email alerts
|

Missing western half of the Pacific Plate: Geochemical nature of the Izanagi‐Pacific Ridge interaction with a stationary boundary between the Indian and Pacific mantles

Abstract: The source mantle of the basaltic ocean crust on the western half of the Pacific Plate was examined using Pb-Nd-Hf isotopes. The results showed that the subducted Izanagi-Pacific Ridge (IPR) formed from both Pacific (180-80 Ma) and Indian (80-70 Ma) mantles. The western Pacific Plate becomes younger westward and is thought to have formed from the IPR. The ridge was subducted along the KurileJapan-Nankai-Ryukyu (KJNR) Trench at 60-55 Ma and leading edge of the Pacific Plate is currently stagnated in the mantle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 124 publications
(448 reference statements)
3
34
0
4
Order By: Relevance
“…[] and Miyazaki et al . [], which is consistent with the classification made by Nd‐Hf isotope systematics in Figure 11. Small number of equatorial Atlantic MORBS may also be from Pacific DMM.…”
Section: Formation Of the Solid Earth's Chemical Componentssupporting
confidence: 90%
See 1 more Smart Citation
“…[] and Miyazaki et al . [], which is consistent with the classification made by Nd‐Hf isotope systematics in Figure 11. Small number of equatorial Atlantic MORBS may also be from Pacific DMM.…”
Section: Formation Of the Solid Earth's Chemical Componentssupporting
confidence: 90%
“…The proposed stationary boundary between Indian and Pacific upper mantles in Figure a is from Miyazaki et al . [].…”
Section: Formation Of the Solid Earth's Chemical Componentsmentioning
confidence: 99%
“…Liu et al () suggested that the distribution of low‐velocity anomalies below Asia is consistent with such an extrusion of mantle and they showed with numerical models that the continuous injection of mantle underneath the India‐Asia collision zone over the past 50 Ma could result in such an extrusion of mantle toward the east. Miyazaki et al () suggested instead that the boundary between the Indian and Pacific mantles has been stationary in the western Pacific since the Cretaceous. The long‐term subduction of the Tethys Ocean below the southern margin of Asia before collision may thus have allowed such an invasion on Indian mantle before collision started.…”
Section: Discussionmentioning
confidence: 99%
“…[] and Miyazaki et al . [], which is consistent with the classification made using the Nd‐Hf and Pb isotope systematics by Kimura et al . [] and the additional examination in Figure 6 of this paper.…”
Section: Implications For Mantle Dynamicsmentioning
confidence: 99%
“…In contrast, more than half of the Pacific mantle domain originated from PM younger than the average depletion age of 1.3 Ga old DMM (Figure a). The boundary between these two domains appears to have been stationary since the Mesozoic [ Mahoney et al ., ; Miyazaki et al ., ; Nebel et al ., ]. The more than half of the upper mantle in the NAIP appears to contain a large EDR component with depletion age <0.8 Ga, similarly young as in the Pacific mantle domain.…”
Section: Implications For Mantle Dynamicsmentioning
confidence: 99%